(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2015)
In the paper Il nomotropismo di Antigone Antigone’s behavior is looked from the perspective of nomotropism or acting with reference to rules (the word ‘nomotropism’ is a neologism coined by Amedeo Giovanni Conte). In particular, the first part of the paper explores in the perspective of nomotropism the meaning of verses 902-912 of Sophocles’s Antigone. The second part of the paper deals with the paradoxical aspect of Antigone’s nomotropism. Nel saggio Il nomotropismo di Antigone, il comportamento di Antigone è interpretato alla luce del concetto di nomotropismo o agire in relazione a norme (il termine ‘nomotropismo’ è stato coniato da Amedeo Giovanni Conte). In particolare, la prima parte del saggio indaga alla luce del fenomeno del nomotropismo i versi 902-912 dell’Antigone di Sofocle. La seconda parte del saggio ha per oggetto il carattere paradossale del comportamento nomotropico di Antigone.